Socio-Economic Importance of Tree Nurseries in Eldoret Municipality, Uasin Gishu County (Kenya) - Rutto, G. C.; Odhiambo, K. O. (Africa Environmental Review Journal, 2017)
Tree nurseries in urban areas are a major source of planting materials for afforestation and associated ecosystem services including carbon stock accumulation in both urban and rural landscapes. The practitioners, however, operate under informal (and sometimes illegal) land tenure with those establishing tree nurseries by the roadside and on road reserves being common. The socio-economic benefits of such urban tree nurseries have not been well documented and appreciated and the growers are generally perceived to be engaged in a last resort economic activity. This study was done to determine Socio-economic importance of tree nurseries in Eldoret Municipality (Kenya). Specific objectives were to: (i) identify tree species being raised in tree nurseries within Eldoret Municipality, (ii) determine the monetary value and market sources for the tree seedlings raised in the Municipality, (iii) quantify contribution of tree nursery enterprise to the provision of employment opportunities in Eldoret Municipality, and (iv) identify the challenges facing the tree nursery business. Stratified random sampling of urban tree nurseries was done and semi-structured questionnaires administered to the nursery head persons at 30% sampling intensity. A large proportion (86.1%) of tree nursery owners in Eldoret Municipality are young (between 18 and 43 years) and have attained post primary level of education (64%). There is gender parity with regards to proprietorship of tree nursery enterprise in Eldoret Municipality. The tree nurseries are of great socio-economic importance. Twenty nine (29) tree species are grown in the nurseries and the main ones are Cupressus lusitanica (10.4%), Callistemon spp (9.75), and Grevillea robusta (9.3%). Ninety seven percent (97.2%) of the tree nursery owners had employees, and the tree nurseries in the Central Business District put together generated Ksh 7.5416 million per production cycle. The tree nursery owners however experienced the following challenges (by % respondents): water shortage (24%), theft (17%), market related problems (13%) and Evictions by municipal authorities (9%). Recommendations on the enterprise land tenure and the proprietors’ capacity building have been made.